Charge ordering at low temperature in lithium manganese oxide spinel. (January 2020) - Panca Putra, T.Y.S.; Yonemura, M.; Torii, S.; Kamiyama, T.
Abstract: Spinels lithium manganese oxide LiMn2 O4- δ synthesized from mixtures of different raw materials were used to study the relationship between the synthesis method and properties of the spinel. The investigation was emphasized on phase transition in lithium manganese oxide spinel compound at low temperature studied by means of neutron powder diffraction. It is found that the cubic structure of LiMn2 O4- δ, synthesized from Li2 CO3, with space group Fd-3m at room temperature was distorted to orthorhombic symmetry with space group Fddd at 290K and become more obvious down to 10K, where the splitting indicates the structural transition close to tetragonal. The equal proportion of coexisted Mn 3+ (Jahn-Teller) and Mn 4+ ions is associated with partial charge ordering. It is also found that the sample synthesized from LiOH.H2 O and MnO x does not show phase transition at low temperatures. The extent of orthorhombic distortion is related to oxygen vacancy, δ, which is affected by the synthesis method such as the choice of starting materials, mixing method and annealing temperature.